Studi Kasus Penggunaan Cognitive Behavior Therapy (CBT) dalam Menurunkan Tingkat Depresi pada Wanita Dewasa - Juliana Hindradjat; M. Ramli; Carolina Ligya Radjah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The purpose of this study was to determine whether Cognitive Behavior Therapy (CBT) is effective in reducing depression in adult women. This qualitative research used a case study approach with three adult female respondents. The research data were obtained through observation, interviews, and measuring the level of depression using the BDI-II (Beck Depression Inventory-II) and MCMI-IV (Millon Clinical Multiaxial Inventory-IV) measuring instruments. The BDI-II scale score data and the MCMI-IV scale before and after the intervention were then compared. The results of the analysis of this study showed that CBT can reduce the level of depression and that is indicated by a decrease in the score from indicated severe to not indicated in clinical syndrome of persistant depression and major depression on the MCMI-IV scale. Measurements using the BDI-II scale also showed a change in the level of depression from major depression to minimal depression. The measurement results of these two tests were also confirmed by changes in mood, cognitive function and behavior.